Utvikling av et manualbasert verktøy for veiledning av studenter i praksis - et bidrag til å styrke kvaliteten på utdanningen - Høium, Kari; Tørris, Christine (Nordisk tidsskrift for helseforskning, 2019)
Clinical training in health and social care educations are important in the development of professional competence of students. However, clinical supervisors may be uncertain of their own counselling skills, and how to meet the students’ needs in their clinical practice. Here, a manual-based counselling guide, developed through counselling courses for clinical supervisors, is presented. The counselling guide is based on data from guidance courses, and the supervisors’ needs in strengthening their counselling skills.
Keywords: counselling; students; placement counselling; placement counsellor; quality improvement; manual based tool; counselling skills; veiledning; studenter; praksisveiledning; kvalitetsforbedring; manualbaserte tiltak; veiledningsferdigheter